2019
DOI: 10.1097/ijg.0000000000001364
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Degradation of XEN45 Gel Stent 3 Years After its Implantation

Abstract: Introduction: We report a case of XEN45 Gel Stent removal 3 years after its implantation. The stent had degraded with a closed lumen, so a new stent was implanted. Case Report: A 63-year-old woman was scheduled for XEN45 Gel Stent implantation. Three years after the primary surgery and 2 years after a surgical revision, second revision surgery was required. The conjunctiva was opened, and the implanted XEN Gel Stent was stripped of the adhesive scar tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Thirdly, the material and design of the two implants differ, which may possibly have different effects on biocompatibility, foreign‐body reaction and migration after implantation. Widder et al (2019) recently published a case report of stent degradation after Xen implantation. The long‐term effect of these materials in glaucoma patients is yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the material and design of the two implants differ, which may possibly have different effects on biocompatibility, foreign‐body reaction and migration after implantation. Widder et al (2019) recently published a case report of stent degradation after Xen implantation. The long‐term effect of these materials in glaucoma patients is yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications that have been reported in the context of XEN ® 45 implantation procedures were device fracture during needling [20], endophthalmitis [21], or degradation of the device [22], but we are happy to report that none of them occurred in our case series, nor was there any procedural failure (defined as presence of a secondary IOP lowering procedure or loss of light perception) [18] during the three-year follow-up period that made it necessary to replace the gel stent. Comparing our outcomes with other studies found in the literature, De Gregorio [16] (XEN ® 63 implantation procedures) reported an 11.8% failure rate, whereas Lenzhofer had 10% of failed XEN ® 63 implantation surgeries [18].…”
Section: Discussionmentioning
confidence: 99%
“…Widder et al 61 presented a 63-year-old woman with Xen implant requiring revision 3 years after surgery after having had two failed previous revision. At the time of revision, the conjunctiva was opened and the implant was stripped of the adhesive scar tissues.…”
Section: Degradationmentioning
confidence: 99%